Osteoarticular tuberculosis in Central India: Changing epidemiological profile and emerging challenges - Vivek Kumar Kori; Deepanshu Bandil; Mohit Asthana; Deepak Singh Maravi (International Journal of Mycobacteriology, 2023)
Background: Osteoarticular tuberculosis (OATB) is a form of extrapulmonary tuberculosis (TB) affecting bones and joints. There is a paucity of data on skeletal TB epidemiology in the annual TB reports and current literature. Many atypical presentations of the disease have also emerged. This necessitates periodic observation of the epidemiological profile of OATB. The aim of this study is to analyze the prevailing epidemiological trends of OATB in Central India. Methods: The 5-year ambispective observational study was conducted at the department of orthopedics of a tertiary care center in Central India. Records of patients diagnosed with OATB from January 2017 to December 2021 were analyzed for demographic factors, site of lesion, comorbidities (pulmonary TB, human immunodeficiency virus, and diabetes), etc., Chi-square test for linear trend was used to determine whether a linear trend exists in the number of diagnosed cases. Results: Two hundred and ten skeletal TB lesions were found in 208 patients included in the study. OATB was highly reported in young adults and females. Spinal lesions were three times more common than extraspinal OATB lesions. The lumbar spine was the most affected region. Hip was the most common extraspinal site. Unusual sites such as sternoclavicular joint and ischial tuberosity were also involved. Conclusion: The burden of OATB is increasing, especially spinal TB. The involvement of atypical sites insists on strong clinical suspicion for early diagnosis. The practice of empirical antitubercular chemotherapy needs to be reviewed considering the risk of drug resistance.